The incidence of chronic drug-induced liver injury: a systematic review and meta-analysis - Zhang, Yu; Ren, Yu-Lin; Song, Xiang-Rui; He, Xi-Jie; Wen, Xiao-Yu (Frontiers in Pharmacology, 2026)
ObjectivesDrug-induced liver injury (DILI) is a recognized adverse drug event. Although most cases present with acute hepatic damage, evidence indicates that a proportion progress to persistent liver injury. The absence of a standardized definition for chronic DILI has contributed to significant discrepancies in reported incidence rates across clinical studies. This meta-analysis aims to determine the pooled incidence of chronic DILI, providing robust epidemiological evidence.MethodsThis meta-analysis was conducted in accordance with the PRISMA and MOOSE guidelines. A systematic search was conducted in PubMed, Web of Science, Embase and Cochrane Library databases from their respective inception dates to 11 July 2025. The quality of cohort studies was assessed using the NOS. A random-effects model was used to calculate the pooled incidence of chronic DILI, expressed as corresponding 95% confidence intervals (CIs). Subgroup analyses were performed to explore potential sources of heterogeneity. Publication bias was assessed and sensitivity analyses were conducted. All statistical tests were two-tailed, and a P value <0.05 was considered statistically significant.ResultsA total of 24 studies were included in the final analysis. The pooled incidence of chronic DILI (based on a duration of liver injury lasting more than 6 months without distinguishing the suspected drugs) was 14.09% (95% CI: 10.35%–18.29%; I2 = 80.76%). Four studies that reported the incidence of chronic DILI based on a 12-month follow-up (without distinguishing causative drugs) showed a pooled incidence of 7.95% (95% CI: 5.16%–11.24%; I2 = 54.8%). The pooled incidence of chronic DILI attributed to antimicrobial drugs (6-month follow-up) was 14.56% (95% CI: 10.86%–18.65%; I2 = 0%).ConclusionChronic DILI accounts for a clinically certain proportion of DILI cases. Greater emphasis should be placed on the long-term management and follow-up of patients with DILI to mitigate the risk of chronic progression.Systematic Review Registrationhttps://inplasy.com, identifier INPLASY202580021.